Writing as a Magician's Game:The Strange Early World of Christoph Meckel - Heidi M. Rockwood (Studies in 20th & 21st Century Literature, 1984)
The contemporary German author Christoph Meckel often introduces into his early short stories the metaphor of "playing a game" for creating a literary work. The paper investigates how Meckel uses this metaphor, what types of games he plays with the reader, and what kind of a world he creates through those games. On the basis of four short stories it suggests the conclusion that Meckel often introduces dangerous overtones and consequences, even though he likes to present himself as a happy and harmless storyteller, and that his stories share many characteristics with dreams and nightmares. Nevertheless, such game-playing is an important and positive activity, for it fulfills a definite social purpose. In the longer story "In the Land of the Umbramauts" Meckel describes a society in which the ability to play creatively has been lost. While the Umbramauts are not totally to blame for this situation, theirs is described as a society without hope. Despite the possible dangers inherent in play, Meckel seems to warn us: it is far more dangerous not to play, since it may lead to the loss of our basic humanity. It is a warning that he himself has heeded: his works continue to confront the reader with the elements of play and surprise.
Keywords: Christoph Meckel; metaphor; playing a game; writing; reader; short stories; consequences; storyteller; dreams; nightmare; In the Land of the Umbramauts; society